Investigating the Relationship between Social Capital and Awareness of Citizenship Rights Emphasizing the Mediating Role of Political Capital and Economic Capital (Case Study: Citizens of Ahvaz) - saleh salehi; Ali Hussein Hosseinzade; yousef amini (توسعه اجتماعی)
Awareness of the rights and duties of citizenship and active participation of citizens in society is one of the challenging issues. The present study investigates the relationship between social capital and awareness of citizenship rights among citizens of Ahvaz. The research method is mixed type "quantitative descriptive survey type and qualitative field type with in-depth interview". In the qualitative part, the data foundation method has been used to theorize the data based on interpretive-constructive foundations. The statistical population of the study was all citizens aged 20 to 65 years living in Ahvaz. Using cluster random sampling, 526 of these citizens were selected as the sample. In this study, in-depth interviews, researcher-made questionnaires on citizenship, social capital, political capital, economic capital and demography were used to collect information. Atlas.ti software was used for qualitative data analysis and SPSS and AMOS software were used for quantitative data analysis. The research findings indicate that there is a significant relationship between social capital, political capital and economic capital and awareness of citizenship rights. In general, significant relationships were obtained between research variables and the research model was approved. It seems that the level of awareness of citizenship rights with respect to the significant relationship with social capital, political capital and economic capital, as an important and influential variable can provide the context for the welfare and political, economic and social development of the target community.